Perancangan dan Simulasi Sistem Kendali Destilasi Air Laut Berbasis ESP32 dengan Sumber Energi Surya dan Bayu - Rival Nur Alamsyah (GLOBAL SCIENTS PUBLISHER, 2026)
The clean water supply crisis in coastal areas requires a seawater treatment system that can operate independently and adapt to fluctuations in renewable energy. This study aims to design and verify an ESP32-based seawater distillation control system that utilizes a combination of solar and wind energy. The research method uses an engineering design approach and digital simulation through the Wokwi platform. The system integrates an HC-SR04 ultrasonic sensor for water volume estimation, a DHT22 sensor for temperature reading, a potentiometer to represent changes in solar panel and wind turbine power, a servo motor to represent a pump or valve actuator, an LED as a heater indicator, and a 20x4 LCD as a monitoring interface. The control algorithm uses water level hysteresis at the 10–70 liter range, a safety interlock with a minimum power of 50 W, and heater control with a lower temperature limit of 50°C and an upper temperature limit of 80°C. Simulation results show that the servo moves to the 90° position when the water volume is ≤10 liters and returns to the 0° position when the volume reaches ≥70 liters. The heater is deactivated when the total power is less than 50 W, activated when the temperature is ≤50 °C and the power is sufficient, and turned off when the temperature reaches ≥80 °C. The simulation validates the basic functions of water level control, energy management, and temperature protection according to the designed logic. This system can be the basis for developing a hardware prototype for managing renewable energy-based seawater distillation.